The national and provincial prevalence and non-fatal burdens of diabetes in China from 2005 to 2023 with projections of prevalence to 2050 - Yu-Chang Zhou; Jiang-Mei Liu; Zhen-Ping Zhao; Mai-Geng Zhou; Marie Ng (Military Medical Research)
Abstract Background China accounts for one-quarter of the world’s diabetes population, with significant subnational disparities. However, none of the available data have provided comprehensive estimates and projections at both regional and national levels in diabetes prevention and management. This study aimed to explore the temporal trends and geographical variations in the prevalence and non-fatal burden of diabetes by age and sex across China from 2005 to 2023, and to forecast diabetes prevalence through 2050. Methods We conducted a population-based study based on the nationally representative surveys, and literature reviews. Using the DisMod-MR model and Chinese-specific disease disability weights, we estimated the non-fatal burdens of diabetes, including prevalence and years lived with disability (YLDs), across sexes, age groups, and locations. The temporal trend change was measured as the average annual percent change. The effect of the Human Development Index on burdens was assessed by applying Spearman’s rank correlation analysis. We further projected diabetes prevalence to 2050 under two scenarios, the natural trend and the effective intervention on body mass index (BMI). Results In 2023, an estimated 233 million individuals in China were living with diabetes. Compared to 2005, the age-standardized rate (ASR) of prevalence has increased by nearly 50%, from 7.53% (95% CI 7.00–8.10%) to 13.7% (95% CI 12.6–14.8%) in 2023. The ASR of YLDs was estimated at 19.1 per 1000 population (95% CI 18.6–19.5) in 2023, compared to 10.5 per 1000 population in 2005. The ASR of prevalence and YLDs was consistently higher in males than in females. The provinces with the highest diabetes prevalence and disease burden were Beijing, Tianjin, and Shanghai. Our forecast results suggest that if existing trends continue, the prevalence of obesity will reach 29.1% (95% CI 22.2–38.2%) nationally by 2050, with some provinces in the northern region observing a prevalence of over 40%. Conversely, if effective obesity interventions were implemented, the growth in diabetes prevalence could potentially be suppressed by nearly 50%. Conclusions The health burden and economic cost associated with diabetes are profound. There is an urgent need to scale up preventive efforts and improve population awareness to enhance disease management and achieve optimal treatment outcomes.